Is earnings management related to labor productivity gap? Evidence from the USA - Rafiqul Bhuyan; Fuad Hasan (Journal of Risk and Financial Management, 2022)
Using a standard partial adjustment model and US firms, we study the relationship between managers' failure to achieve target labor productivity and their tendency to manage earnings. To overcome the endogeneity problem, we employ an instrumental variable technique based on negative investment growth and find that managers, experiencing a labor productivity gap, tend to manage earnings by manipulating discretionary accruals and real operating activities. Additional analysis suggests that elements of personal value maximization biases drive the estimated effect of the labor productivity gap. Our results are robust considering variation and alternative measures of statistical sensitivity. The positive association between the labor productivity gap and earnings management is also consistent with the opportunistic financial reporting hypothesis and impression management theory.
Keywords: 650; accruals; earnings management; labor productivity gap; real activities manipulation